Path Analysis and Theory of Planned Behavior on Using PAP SMEAR as Early Detection of Cervical Cancer in Sewon I Community Health Center, Bantul, Yogyakarta, Indonesia - Fatimah Dewi Anggraeni; Bhisma Murti; Ruben Dharmawan (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Cervical cancer patients per hour has increased by 2.5 people. Women died because of cervical cancer are 1.1 per hours. Indonesia is the second country after Tiongkok with the largest number incidence of cancer. Pap smear is one of the screening programs to reduce the numbers of cervical cancer genesis. Moreover in Indonesia, the rates of screening Pap smear less than 5%. This study aimed to investigate path analyze of using pap smear with as early detection of cervical cancer by planned theory of behavior in women in Sewon 1 Public Health Center, Bantul.Subjects and Method: This was an observational analytic study with the direction cross sectional design. A total sample of 96 women with comprised 32 cases and 64 control with fixed-disease sampling method. Data analysis used path analysis.Results: The results show there is influence between intentions and screening Pap smear (p=<0.000), perceived behavioral control with Pap smear test (p=0.010). An indirectly interaction with the screening Pap smear through intention on attitudes (p=<0.001), subjective norms (p=0.036), and control behavior perceptions (p=0.034).Conclusion: from this study there are interactions directly and indirectly the uses of screening Pap smear based on planned of behavior theory.Keywords: Planned of behavior theory, screening pap smearCorrespondence:Fatimah Dewi Anggraeni. School of Public Health, Graduate Program, Sebelas Maret University, Surakarta.Journal of Health Promotion and Behavior (2016), 1(1): 1-8https://doi.org/10.26911/thejhpb.2016.01.01.01